TAXONOMIC PROBLEMS ON FOUR SPECIES OF PONTELLA (COPEPODA, CALANOIDA) DESCRIBED BY A. SCOTT (1909) IN INDO-MALAYAN WATERS - Mulyadi (Treubia, 2014)
Four species of Pontella, i.e., P. alata, P. cerami, P. denticauda, and P. forficula, which were originally described by A. Scott (1909) were found from Indo-Malayan waters. Some misidentifications resulting in wrong species identity were discovered on P. cerami and P. forficula. Pontella cerami A. Scott, 1909, described based on two male specimens from the Banda Sea, Indonesia is here recognised as the male of P. alata. Similarly, P. forficula, also known from two male specimens from the Sulu Sea, Philippine must be reassigned as the male of Ivellopsis elephas (Brady, 1883). Another Indo-Malayan Pontella, i.e., P. denticauda A. Scott, 1909 must also be moved to the genus Ivellopsis Claus 1893, as Ivellopsis denticauda (A. Scott, 1909) by its having posterior corners of Pdg5 produced into rounded lobes in both sexes; particularly in the female, by (1) the genital double-somite with a large lateral process, (2) the CR asymmetrical with the right ramus longer than the left, and (3) the Re of P5 with 3 apical spines and with an acuminate Ri. The male has, (1) the CR asymmetrical with right ramus slightly longer than the left, and (2) the thumb of Re2 of right P5 is elongated, and (3) the Re2 of the left P5 bifurcate at apex. Descriptions, measurements and figures of the four species are given, along with a review of their distribution and that of their species groups over Indo-West Pacific waters, together with taxonomic remarks and synonymies in each case.